Blood types and their relationship to personality traits among students of the Faculty of Arts, University of Sebha - Abu Bakr سليمة ابراهيم; Ahmed إبراهيم أحمد حمزة (Journal of Human Sciences, 2022)
This study aims to know the blood types and their relationship with personality traits among students of the Faculty of Arts, University of Sebha, Sabha city. The sample size was (64) male and female students. The Brofeel modified personality profile scale was used for "Gordan" as a study tool. The (T) test was used as a statistical method for it. Its results were as follows: the hypothesis was fulfilled that confirms the existence of statistically significant differences between males and females in both the poise, emotional trait and the leadership trait in each of the two chapters (AB and B), It is a statistically significant function at the level of significance (0.05). However, there are no statistically significant differences between members of the total sample according to their different factions, and between the male sample members according to their different factions. From one side, and between the female sample members according to their different factions, and between males and females in both the responsibility trait and the social trait with all factions. There are difference with the trait of balance, emotion and trait leadership in each of the two classes (o, A)